Doing Case Study Research Collaboratively: The Benefits for Researchers. (29th April 2022) - Mcclunie-Trust, Patricia; Jones, Virginia; Winnington, Rhona; Shannon, Kay; Donaldson, Andrea E.; Macdiarmid, Rachel; Jarden, Rebecca J.; Turner, Rosemary; Merrick, Eamon; Andersen, Patrea
Collaborative research teams are an effective strategy to combine the knowledge and skills of like-minded researchers across tertiary education settings and international borders. Research collaborations have the potential to increase research capacity for both individuals and the team alike. The purpose of the study was to explore the experiences and perceptions of a team of seven Australasian nurse academics undertaking a longitudinal multi-site case study. We used a nominal group technique in this deductive qualitative exploratory study. The key findings from this study indicate establishing safe academic relationships is paramount to successful collaborative teams. Collaborative research teams offer opportunities to learn research processes from other members through sharing of expertise and skillsets, together with upholding a positive engagement with technology to ensure full research participation is achievable irrespective of geographical location. To conclude, in this study we have identified multi-site collaborative research teams provide an opportunity to leverage the strengths of individuals to enhance research outcomes across organisations. The synergistic effect of the team builds research blue skies thinking and capacity building through mentorship and support. The potential for positive change through mentorship and support, alongside the forged new relationships, are all key drivers of researcher wellbeing, never more important as we transition into new ways of working both now and into the future.